(untitled) (The Conference Hub, 2025)
Politeness Theory has played a central role in explaining how speakers manage social relationships through language. Closely connected to this framework is sociopragmatics, which focuses on the social and cultural norms governing appropriate language use in context. This article examines the theoretical foundations of Politeness Theory, particularly Brown and Levinson’s face-based model, and explores its relationship with sociopragmatics. The discussion highlights how sociopragmatic variables such as power, social distance, and imposition shape politeness strategies across cultures. The article also reviews key criticisms of Politeness Theory and considers its pedagogical implications for second language teaching. It is argued that integrating sociopragmatic awareness into language instruction is essential for developing learners’ communicative competence and avoiding pragmatic failure.